Cost-Tiered GPS Unit Three-Dimensional Capability Comparisons and Testing - Vickroy, Bryan; Hon, David (My University, 2012)
Handheld Global Positioning System (GPS) units are thought to be less accurate than professional grade GPS units, but little research has been done to determine the three-dimensional accuracy of equipment grade in terms of cost. By collecting three-dimensional geospatial data with multiple GPS units of differing grade, digital elevation models can be created to compare and analyze the degree of accuracy of each unit. The Garmin eTrex, Garmin Montana, and Trimble XR models were taken into the field to create base data to be converted into three-dimensional elevation models. These GPS units range in value from thousands of dollars (Trimble XR) to just a couple hundred dollars (Garmin eTrex). The three created elevation models will then be compared to each other, as well as USGS elevation maps, to see which models are most accurate and consistent to the known base elevations.
Color poster with text, images, and tables.
Keywords: Global positioning system--Cost effectiveness; Three-dimensional display systems--Evaluation; Posters